Strategi Badan Keamanan Laut dalam Penegakan Hukum Terhadap Tindak Pidana Bidang Kelautan - Triadi, Irwan; Ardian, Muhammad Fadhil (Innovative: Journal Of Social Science Research, 2024)
Indonesia is an archipelago that has abundant natural resources, especially in the Indonesian sea area. The importance of marine functions often leads to various violations of the law. The research entitled “The Role of The Maritime Security Agency in Law Enforcement of Maritime Crimes” has the formulation of the problem, namely how law enforcement is carried out by the maritime security agency to minimize criminal acts in Indonesian sea areas. The purpose of this study is to determine the role of The Maritime Security Agency in law enforcement against marine criminal offenses. The method used in this study is normative legal research. Conclusions on the research is The Maritime Security Agency has a function to synergize law enforcement in the Indonesian sea area. The Law Number 32 of 2014 about maritime affairs has a weakness because The Maritime Security Agency is not mandated to have a state-flagged ship to do hot pursuit and also the Maritime Security Agency is not overwritten with investigative authority. This resulted in the law enforcement process not being in line with the principle of justice which is fast, simple, and low cost.